Seagrass space occupation efficiency is key for their role as ecosystem engineers and ecological indicators - Vieira, Vasco M. N. C. S. (2024)
Studies for the preservation of seagrass beds biotopes have met difficulties in establishing appropriate methods assessing their health. We tested the efficiency of space occupation by seagrasses scattered worldwide (dgrass index), which proved to be dependent on clonal growth form and morphometric plasticity. dgrass correlated with the above-ground to below-ground biomass ratio. However, the latter was misleading when high ratios resulted from low below-ground biomass. Nutrient Posphate-limitations were revealed in situations of theoretical Nitrogen-limitation. Enhanced nutrient supply benefitted seagrasses only up to a threshold after which it became detrimental. Better nurtured, healthier meadows with denser canopies increased the organic matter in the sediment and had associated greater abundances of benthic macrofauna. Hence, seagrass biotopes could benefit from moderate anthropogenic nutrient additions. However, organic matter above ≈6% and/or reduced riverine discharges (dams upstream and climate-change-related droughts) were detrimental to healthy meadows, jeopardizing ecosystem services such as macrofauna abundances and carbon sinks.